EMPOWERING MSMES IN SOUTHERN SUMATRA THROUGH SMEXPO PALEMBANG 2025 IN SUPPORT OF SDG 8: STRENGTHENING MARKET ACCESS AND INCLUSIVE ECONOMIC GROWTH - Arief Wibowo Wibowo (RADJA PUBLIKA, 2026)
Empowering micro, small, and medium enterprises (MSMEs) is a crucial strategy for strengthening local economies and supporting the achievement of Sustainable Development Goal (SDG) 8 on inclusive economic growth. This community engagement program was implemented through SMEXPO Palembang 2025, held on 17–19 October 2025 at Palembang Square Mall. The activity involved 27 active MSMEs from the Southern Sumatra region and aimed at expanding market access, enhancing marketing capacity, and strengthening business networks. The implementation methods included a product exhibition (expo), branding and digital content workshops, direct booth-based mentoring, and multi-stakeholder collaboration involving academics, industry, local government, and business communities. The results indicate an improvement in MSME capacity in terms of branding, product display arrangement, digital literacy, and marketing communication. In addition to qualitative impacts, the program generated an economic turnover (Gross Merchandise Value/GMV) of IDR 128,758,952 over the three-day event. Overall, SMEXPO Palembang 2025 made a tangible contribution to strengthening the MSME ecosystem and aligned with SDG 8 by creating more inclusive and sustainable economic opportunities.